Respiratory Protection Programs (RPP) Implementation at Production Unit of A Tin Smelter at Bangka Belitung Islands Province (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
The fume generated from the reaction of flux and molten tin produces tin compounds in the atmosphere which potentially lead to stanosis or also known as tin pneumoconiosis after chronic inhalation and prolonged exposure in the workplaces e.g. in smelter industries. The risk can be minimized by implementing Respiratory Protection Program (RPP). This study aimed to evaluate the implementation of RPP at one smelter industries in Bangka Belitung Province. This is a evaluation study that qualitatively evaluate the implementation of RPP. eigth RPP elements from National safety Council (NSC) Australia was used as guideline. The secondary data from Occupational Health and Safety inspection and monitoring report at one of tin smelter from Department of Manpower (Disnaker), Banga Belitung Island province. It was found that several RPP elements have not been fully implemented, which were (1) compliance with respirator standards, (2) no selection of respirators procedure, (3) no protective clothing, (4) no fit testing execution, (5) improper management of cleaning and inspections, and (6) no evaluation of respirator usage. Moreover, specific work process that need Supplied Air Respirator (SAR) has not been anticipated, and improvement in the training materials, periodic training schedule and evaluation of the Respiratory Protection Program were emphasized. There were 3 informants in this study consisting of company managers, safety officers, and labor inspector. The implementation of RPP at PT X. Tin needs to be enhanced. Continuous coaching, monitoring, inspection, and evaluation related to the Respiratory Protection Program must be carried out more intensively both internally and externally from the government.